Ethnolinguistic Information about RUGYS (Rye) in Lithuanian Dialect Dictionaries - Sakalauskienė, Vilija (Vilnius University Open Series, 2021)
The article analyzes what ethnolinguistic information about rye can be read in the entries of Lithuanian dialect dictionaries. The research data were selected from thirteen dictionaries of Lithuanian dialects and the comprehensive Lietuvių kalbos žodynas (Dictionary of the Lithuanian Language). Thus, dialectal dictionaries are an excellent source of lexical semantic research based on the research methodology of the linguistic image of the world. The research presented in the article was inspired by the Słownik stereotypόw i symboli ludowych (SSiSL) (Dictionary of Folk Stereotypes and Symbols) published by the Lublin Ethnolinguistic School.An attempt is being made to find an answer to the question whether rugys (rye) is just a source of food and a basis for biological existence for Lithuanian farmers and rural residents? It is assumed that rye is synonymous with bread as a gift from God to farmers. According to folklore sources, people sacrificed the best stook of rye to God. According to the tradition of the Polish people, rye is a symbol of abundance, wealth, kindness; according to the tradition of the Lithuanians it is a symbol of growth, vitality, fertility and endurance.Analyzing the data of Lithuanian dialect dictionaries and the Dictionary of the Lithuanian Language it was established that the lexeme rye is used in various parts of lexicographic articles: 1) as a title word in dictionary entries; 2) in definitions and illustrative sentences; 3) in the illustrations of entries of other words (for example, crops, grain, shoot, winter crops); 4) in terminological compounds (e. g. African rye (Secale africanum), annual cereal (Secale cereale), cereal grass (Secale sylvestre); 5) in paremias; 6) in phraseological compounds.The lexicographic definition of the lexeme rye highlights the following features of the category: a plant, eared (various properties: winter crop, upright, strong, dense, etc.), a symbol of everyday life. The illustrative examples of the words reflect man’s respect for rye as a plant that gives bread.
Keywords: Rye; linguistic view of the world; ethnolinguistics; dialectal dictionary; definition